Costs and effectiveness of standard treatments applied to flexible and rigid pavements: case study in Indiana, USA. Issue 1 (27th July 2018) - Qiao, Yu; Labi, Samuel; Fricker, Jon; Sinha, Kumares C
Abstract : Highway agencies apply rehabilitation and maintenance treatments to restore pavement condition and to reduce the deterioration rate, thereby extending pavement longevity and ultimately deferring reconstruction. Before agencies make decisions regarding the need for some treatment, treatment selection and timing and repair schedule (combination of treatment types and timings), the costs and performance effectiveness associated with each treatment must be known. In addition, agencies seek to identify and comprehend the factors that influence the costs and performance effectiveness of their standard treatments. This paper uses data from a Midwestern state in the USA to develop cost and effectiveness models for a number of treatments. In doing so, this study selects appropriate response variables, determines values of these outcomes for each pavement section under study and estimates the outcome models as a function of attributes related to the pavement and treatment. The paper confirms that treatment effectiveness is influenced by the pre-treatment pavement condition. In addition, the treatment average unit costs are influenced by the project size, road functional class and the pre-treatment pavement condition. The study also quantifies the sensitivity of the cost economy of scale to the dimensions of the treatment project.